2000
DOI: 10.1359/jbmr.2000.15.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Sodium-Dependent Phosphate Transport and Signaling Mechanisms Induced by Basic Fibroblast Growth Factor in MC3T3-E1 Osteoblast-like Cells

Abstract: Physiological and pathological observations indicate that basic fibroblast growth factor (bFGF) is an important regulator of osteoblastic cell differentiation and in particular of cranial ossification. Experimental evidence suggests that inorganic phosphate (P i ) transport could be an important function of bone matrix calcification. In the present study, we address the influence of bFGF on P i transport activity in MC3T3-E1 osteoblast-like cells derived from mouse calvaria. The results indicate that bFGF is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…FGF2 promotes osteocalcin transcription in rodent and human calvarial osteoblasts (Schedlich et al 1994;Boudreaux and Towler 1996;Newberry et al 1996Newberry et al , 1998Debiais et al 1998). This effect, together with the reported increase in sodium-dependent phosphate transport (Suzuki et al 2000), may contribute to the regulation of intramembranous calcification. Recent in vitro data indicate that FGF18 can act like FGF2 to regulate calvarial osteoblast differentiation in vitro (Shimoaka et al 2001).…”
Section: Biological Functions Of Fgfs In Cranial Bone Formationmentioning
confidence: 80%
See 1 more Smart Citation
“…FGF2 promotes osteocalcin transcription in rodent and human calvarial osteoblasts (Schedlich et al 1994;Boudreaux and Towler 1996;Newberry et al 1996Newberry et al , 1998Debiais et al 1998). This effect, together with the reported increase in sodium-dependent phosphate transport (Suzuki et al 2000), may contribute to the regulation of intramembranous calcification. Recent in vitro data indicate that FGF18 can act like FGF2 to regulate calvarial osteoblast differentiation in vitro (Shimoaka et al 2001).…”
Section: Biological Functions Of Fgfs In Cranial Bone Formationmentioning
confidence: 80%
“…FGF2 and FGF18 stimulate ERK2 phosphorylation, which promotes mitogenesis (Hurley et al 1996;Chaudhary andAvioli 1997, 2000;Shimoaka et al 2001) and down-regulates procollagen gene expression in calvarial osteoblasts (Chaudhary andAvioli 1997, 2000). The protein kinase C (PKC) pathway is involved in the control of sodium-dependent phosphate transport (Suzuki et al 2000) and expression of N-cadherin in calvarial osteoblasts (Debiais et al 2001). Mutations in Fgfr2 that cause Apert syndrome induce constitutive activation of PKC in human calvarial osteoblasts (Fragale et al 1999;Lomri et al 2001).…”
Section: Fgf Signaling Pathways In Intramembranous Bone Formationmentioning
confidence: 99%
“…Following cells treatment with agents, Pi transport activity was determined in Earle's buffered salt solution (EBSS) containing 0.1 µM labeled H 3 [ 32 P]O 4 as previously described [4]. Before the transport assay, the cell layer was rinsed three times with EBSS without radioactive or cold substrate.…”
Section: Influence Of Avp On Pi Transport Activitymentioning
confidence: 99%
“…However, a recent study by Jono et al [2] suggests that aortic vascular smooth muscle cell (VSMC) acquires the phenotype of osteoblast-like cells, and that the expression of inorganic phosphate transporter (PiT) on VSMC is important in the process of vascular calcification. The enhancement of Pi transport in boneforming cells is essential for the mineralization of skeletal tissues [3], and several growth factors and hormones have been reported to stimulate both proliferation and Pi transport [4][5][6][7]. As for VSMCs, it is nowadays well accepted that the proliferation of VSMC plays a crucial role in the pathogenesis of hypertension and atherosclerosis, and is a key event during the formation of intimal hyperplasia after artery injury [1,8].…”
mentioning
confidence: 99%
“…Montessuit et al (1991Montessuit et al ( , 1995 first identified and characterized a phosphate transport mechanism in matrix vesicles isolated from the growth plates of cartilage, and this phosphate transporter was sodium-dependent, sensitive to hormone stimulation and to phosphate deprivation. Recent researchers have reported that sodium-dependent Pi transporters are expressed in osteoblasts and chondrocytes, and are regulated by several factors such as insulin-like growth factor (IGF-1) (Campbell et al, 1992;Palmer et al, 1997), fluoride (Burgener et al, 1995), parathyroid hormone (PTH) (Caverzasio et al, 1996), platelet-derived growth factor (PDGF) (Zhen et al, 1997), protein kinase C (Jobbagy et al, 1999), basic fibroblast growth factor (bFGF) (Suzuki et al, 2000) and extracellular Pi (Kavanaugh et al, 1994;4 Montessuit et al, 1995). Therefore, they have a role in regulating Pi handling in bone forming cells (Palmer et al, 1999;Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%